(untitled) (Research, Society and Development, 2022)
Safflower (Carthamus tinctorius L.) is an herbaceous oilseed with characteristics that allow its cultivation in arid and semiarid regions. Thus, the characterization of different safflower genotypes is an important step in obtaining basic information for improvement programs of this crop. In this context, the objective of this work was to evaluate the genetic divergence among safflower genotypes based on morphological characteristics, in order to provide initial guidelines for breeding programs. A total of 124 genotypes of Carthamus tinctorius L. from the Active Germplasm Bank of the Mato Grosso Cotton Institute and the Plant Genetic Resources Laboratory of the Mato Grosso State University, Caceres Campus, were evaluated. The genotypes were evaluated for 16 morphological characters and the data were submitted to multivariate analysis by the UPGMA grouping method. The estimates of the dissimilarity coefficients ranged from 0.00 to 0.56, indicating the presence of genetic diversity among the genotypes evaluated. The clusters established by the Tocher and UPGMA methods presented differences in the groups formed, completely changing their composition. Thus, there is genetic variability among safflower genotypes evaluated based on morphological characteristics, suggesting the use of these in future combinations in genetic improvement program of the crop.